Relationship between School-Age Abilities in Online Learning with Stress Levels of Parent during the Covid-19 Pandemic - Kartika, K; Mulyati, Sesaria Betty; Lestari, Heni Eka Puji (Universitas Muhammadiyah Surakarta, 2020)
Purpose: Knowing the relationship between abilities at the developmental stage of school-aged children in online learning and levels stress of parents during the Covid-19 pandemic.Methodology: This research used quantitative analysis through cross sectional approach. Data were collected by survey online link questionnaire approximately 3 weeks. This study examined data from parents with at child 6-12 years of age and educated their children in online learning due to COVID-19 Pandemic. The final sample included 126 parents in Madiun City. Data analysis used chi square with = 0.05.Results: The study showed that most parents experienced moderate stress levels as many as 84 respondents (66.7%). The study also showed that there were 52 respondents (66.7%) who were able to follow the online learning process with moderate stress to their parents. Statistical result shows that there is a relationship between ability of school-aged children in online learning to the stress level of parents with p value = 0.002 ( <0.05). It explained that ability of school aged children can increase the stress levels of parents. Conclusion: The Covid 19 pandemic has an impact on the learning process of school age children. Online learning needed an additional role for parents to teached children at home. The ability of school-aged children in online learning affected stress levels of parents. Therefore, intervention for mental health in parents is needed to remain balanced an additional role during COVID-19.